The Risk of Intrauterine Infections in Newborns in Aktobe Region of Kazakhstan - Mamyrbayeva, Marzya Abdramanovna (Asian Journal of Pharmaceutics (AJP), 2017)
Background: The aim of the study was to assess the risk of intrauterine infections (IUIs) in newborns in Aktobe region of Kazakhstan. Materials and Methods: The aggregate data of neonatal mortality in the Republic of Kazakhstan for 2010-2014 years and the rate of neonatal mortality in Aktobe region were analyzed. The retrospective analysis of medical records of 231 mothers was conducted and 938 blood serums probes of infected newborns were analyzed. Results: In the obstetric history of mothers, the most important factors were the following: The spontaneous abortion and non-developing pregnancy, with which the appearance of the liver lesions of the newborn. In somatic status of women, the most frequent pathologies during pregnancy were anemia, chronic foci of infection: Chronic gastritis, chronic pyelonephritis in the exacerbation phase, and chronic adnexitis. However, the violations of fat metabolism in the form of obesity – 9.76% (P = 0.05) and allergic diseases in the form of hay fever – of 19.52% (P = 0.05) were revealed significantly more often in the group of mothers who gave birth to neonates with liver injury. In newborns, the most important factor is the IUI (43.05%) of children. In the neonatal period, 81.6% of infants were diagnosed the central nervous system (CNS) lesion in the form of syndrome of vegetative – visceral dysfunction and the syndrome of depression: A support reflex – 22.2%, a step reflex – 23.6%, the Robinson’s reflex – 18.05%, and others. The conducted ultrasound examination of the brain revealed an increased echogenicity in the region of the thalamus of neonates, which had developed in conditions of hypoxia (chronic placental insufficiency and chronic fetal hypoxia) – 23.6% or with acute intrapartum hypoxia, and the expansion of the cavity of transparent partitions is typical for premature babies – 9.72%. Conclusion: Aktobe is a region with average neonatal mortality rates due to the late mortality, despite the low rate of early neonatal mortality. From all the diseases that took place during pregnancy, that are affecting the manifestation of IUI, there should be noted acute respiratory viral infections (ARVIs), which were registered in 20% cases. Between the event of ARVI and the development of fetal hepatitis were observed an average correlation (r = 0.48). In newborns, the most important factor is the IUI (43.05%) with the CNS lesion of children.